Empowering Farmers with Beauveria bassiana: A training initiative for sustainable pest management and environmental protection - Itji Diana Daud; Tutik Kuswinanti; Kaimuddin Kaimuddin; A. Irma Suryani; Mita Yusri (Jurnal Hasil Inovasi Masyarakat, 2024)
Rice farming in Indonesia frequently faces pest issues, which are typically managed with chemical pesticides that can harm the environment and human health. As an alternative, training on the use of Beauveria bassiana as an environmentally friendly biopesticide was conducted to enhance farmers' knowledge and skills. The training was held in July 2024 with the Mangngu’rangi Farmer Group from Desa Manjapai, Kecamatan Bontonompo, Kabupaten Gowa, South Sulawesi, Indonesia. Prior to the training, 95% of farmers were unfamiliar with B. bassiana, and 100% had not used it. The training methods included lectures, discussions, and hands-on demonstrations. Post-test results indicated that 98% of participants found the training material clear and felt prepared to apply this technology. The training is expected to strengthen farmers' ability to adopt biological control technologies, support agricultural sustainability, and contribute to achieving the SDGs in Indonesia.